1998
DOI: 10.2307/3870644
|View full text |Cite
|
Sign up to set email alerts
|

PCP-A1, a Defensin-Like Brassica Pollen Coat Protein That Binds the S Locus Glycoprotein, Is the Product of Gametophytic Gene Expression

Abstract: Self-incompatibility (SI) in Brassica species is controlled by a single polymorphic locus (S) with multiple specificities. Two stigmatically expressed genes that have been cloned from this region encode the S locus glycoprotein (SLG) and S receptor kinase (SRK). Both appear to be essential for the operation of SI. It is believed that rejection of incompatible pollen grains is effected by recognition events between an as yet unidentified S locus-encoded pollen coating-borne protein and the SLG/SRK. We previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
72
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(75 citation statements)
references
References 54 publications
2
72
0
1
Order By: Relevance
“…However, the position of the fourth conserved cysteine residue from the N-terminal end is different from that of class A proteins of the PCP family (8). Thus, allelic variants of SP11 form a novel class of the PCP family.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the position of the fourth conserved cysteine residue from the N-terminal end is different from that of class A proteins of the PCP family (8). Thus, allelic variants of SP11 form a novel class of the PCP family.…”
Section: Resultsmentioning
confidence: 99%
“…Alignment of the predicted amino acid sequences of the four allelic forms of SP11 revealed that all of their mature proteins contain eight conserved cysteine residues, one of the hallmarks of the PCP family proteins (8). However, the position of the fourth conserved cysteine residue from the N-terminal end is different from that of class A proteins of the PCP family (8).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations